Popular Attitudes toward Free Markets: The Soviet Union and the United States Compared - Shiller, Robert J.; Boycko, Maxim; Коробов, В. П. (American Economic Review, 1991)
Random samples of the Moscow and New York populations were compared in their attitudes towards free markets by administering identical telephone interviews in the two countries in May 1990. Although the Soviet respondents were somewhat less likely to accept exchange of money as a solution to personal problems and although their attitudes toward business were less warm, the authors found that the Soviet and American respondents were basically similar in some very important dimensions: in their attitudes toward fairness, income inequality, and incentives and in their understanding of the working of markets. Copyright 1991 by American Economic Association.